A Peace Memorial - Ulysses Rible::::::::: (1928)
Text on bottom right reads: 'I am a citizen of the United States and will be under 27 years of age on July 1, 1930. Atelier des Noceurs (supervisor - Univ. So. Calif.), first preliminary for 23rd Paris Prize: 'A Peace Memorial''